Influence of Phacoemulsification on Intraocular Pressure in the Eye after Trabeculectomy - Marija Olujić; Dubravka Biuk; Ivana Kotromanović Šimić (Southeastern European Medical Journal)
Aim: The aim of this study was to question whether there is a difference in the change of intraocular pressure (IOP) between groups of participants, achieved by phacoemulsification after trabeculectomy, considering the height of IOP at beginning. As well as whether there is a decreased necessity for topical antiglaucoma (ATG) medications.